2014
DOI: 10.3892/br.2014.279
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective activity of 2-(4-amino-3-chloro-5- trifluomethyl-phenyl)-2-tert-butylamino-ethanol hydrochloride to improve the pulmonary function in asthma

Abstract: Abstract. Asthma is a chronic airway disease that is characterized by significantly exacerbated bronchospasms and marked inflammation of the airways. Although the etiology of asthma remains to be determined, genetic predisposition is one of the factors involved. β 2 -agonists compounds may serve as options for the treatment of bronchial asthma. The aim of the present study was to investigate the effects of 2-(4-amino-3-chloro-5-t rifluomethyl-phenyl)-2-tert-butylamino-ethanol hydrochloride (SPFF) and its enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…It has been reported that (−)-trantinterol and (±)-trantinterol similarly relaxed guinea pig airway smooth muscles precontracted by histamine . Moreover, there was no significant difference among (−)-trantinterol, (+)-trantinterol, and (±)-trantinterol in their activities on cAMP accumulation in asthmatic lung tissues . Therefore, we used symmetric synthesis in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that (−)-trantinterol and (±)-trantinterol similarly relaxed guinea pig airway smooth muscles precontracted by histamine . Moreover, there was no significant difference among (−)-trantinterol, (+)-trantinterol, and (±)-trantinterol in their activities on cAMP accumulation in asthmatic lung tissues . Therefore, we used symmetric synthesis in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Later, compound 1a was proceeded to a series of clinical testing. , A recent phase III clinical study has shown that trantinterol hydrochloride given 50 μg/d orally twice a day was safe and effective and noninferior to procaterol hydrochloride in the studied population of adult Chinese patients with asthma . However, previous biological studies on compound 1a ,, are either short of a systemic structure–activity relationship study or lack of perspectives on the evaluation of the oral bioavailability of the compound and a comparison with existing selective β 2 -AR agonists on β 2 /β 1 -selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, trantinterol [SPFF; 2-(4-amino-3chloro-5-trifluomethyl-phenyl)-2-tert-butylamino-ethanol hydrochloride] bears a novel scaffold of 2-amino-2phenylethanol instead of the classic scaffold of 2-amino-1-phenylethanol and is an example of a novel b 2 -AR agonist under development (Gan et al, 2003). In guinea pigs, (S)-trantinterol was more effective than (R)trantinterol at causing ASM relaxation, despite the observation that there was no significant difference observed for the receptor selectivity of (S)-trantinterol and (R)-trantinterol (Pan et al, 2014). This finding contrasts with the documentation that other (S)-enantiomers are effectively inert at the b 2 -AR (Jacobson et al, 2018).…”
Section: Emerging Classes Of Bronchodilator Drugsmentioning
confidence: 99%
“… 62 Subsequent in vivo experiments showed that (-) SPFF inhibited histamine-induced bronchoconstriction in guinea pigs while (+) SPFF did not. 63 At the time of this writing, there are no registered clinical trials investigating SPFF.…”
Section: Recent Approaches To Ulaba Therapy and Experimental Agentsmentioning
confidence: 99%